ANALISIS DESKRIPTIF SOAL MATEMATIKA PADA SELEKSI PENERIMAAN PESERTA DIDIK BARU SMA/SMK TAHUN AJARAN 2012/2013 DAN 2013/2014 KABUPATEN JEMBER - Nurandari, Devira Ayu; Setiawan, Toto' Bara; Kristiana, Arika Indah (Kadikma, 2015)
Abstract. The goal of this research aims to describe mathematics test on the new students’ environment of senior high and vocational schools in the 2012/2013 and 2013/2014 academic year in Jember. The descriptions are about cognitive level of revised of Bloom’s taxonomy and characteristic of questions. The cognitif level was determined based on the indicators made by the researcher. Validity, reliability, difficulty index, and discriminatory power of the questions were calculated based on the result of the test. Cognitive level, validity, and discriminatory power of the questions in 2012/2013 academic year are bad but its reliability and difficulty index are good. Cognitive level, validity, difficulty index and discriminatory power of the questions in 2013/2014 academic year are bad but its reliability is good. Key words: new students’ environment, revised of Bloom’s taxonomy, characteristic of questions